Chlamydia Infection Between Men and Women: A Cross-Sectional Study of Heterosexual Partnerships. (27th September 2017) - Huffam, Sarah; Chow, Eric P F; Leeyaphan, Charussri; Fairley, Christopher K; Hocking, Jane S; Phillips, Samuel; Tabrizi, Sepehr N; Bellhouse, Clare; Bradshaw, Catriona S; Fehler, Glenda; Garland, Suzanne M; Chen, Marcus Y
Abstract: Background: Studies of sexual partnerships can further our understanding of the sexual transmission of chlamydia, which is important for informing public health interventions and clinical management. The aim of this study was to ascertain among heterosexual dyads the proportion concordantly infected with chlamydia and factors associated with infection between partners. Methods: This study was conducted at the Melbourne Sexual Health Centre between January 2006 and March 2015. Heterosexual partners attending the clinic on the same day were identified prospectively. Dyads where 1 or both individuals were diagnosed with chlamydia by a test performed on the day of joint attendance or within the prior 30 days were included. Testing was by strand displacement assay. Men and women with genital symptoms underwent clinical examination. Results: Of 233 females with chlamydia, 76% (n = 178) of their male partners tested positive. Of the chlamydia-positive females with cervicitis, 91% of males were chlamydia positive. Male infection was less likely if their partner had taken azithromycin or doxycycline within 30 days (7% vs 25%; P = .039). Of 235 males with chlamydia, 77% (n = 178) of their female partners tested positive. No associations were found between male symptoms, signs, or recent antibiotic use and a positive chlamydia result in female partners. Sixty-one percent of the dyads were concordantly infected with chlamydia. Conclusions: These results underscore the high likelihood of heterosexual partners of men and women with chlamydia being infected and the importance that partners are tested and managed appropriately for chlamydia.